Use of monoclonal antibody against human neutrophil elastase in normal and leukaemic myeloid cells. - Pulford, K A (1988)
A monoclonal antibody, NP57, was produced and used against the neutrophil granule protein elastase, which selectively stain neutrophils in cryostat and paraffin wax sections. The antibody stains neutrophils and a subpopulation of monocytes in blood smears and neutrophil precursors in bone marrow smears, and gives positive reactions with the cell lines HL60 and U-937. It labelled the blast cells in 68% of cases of acute myeloid leukaemia (M1-M5) but was unreactive with all cases of lymphoid leukaemias. Most of the elastase negative myeloid leukaemias were labelled by monoclonal anti-myeloperoxidase (antibody MPO-7) as were cells from the promyelocytic line HL60. No cases of myeloid leukaemia showed the opposite pattern--that is elastase positive, myeloperoxidase negative, suggesting that the production of myeloperoxidase precedes the onset of elastase synthesis during myeloid maturation. The anti-elastase antibody NP57 is a useful addition to the range of monoclonal antibodies available for the differential diagnosis of acute leukaemia by alkaline phosphatase-antialkaline phosphatase (APAAP) labelling of cell smears; it may also be of value for the histopathological diagnosis of tumour deposits in myeloid leukaemia and for the detection of neutrophils in paraffin sections.